Comparative environmental and economic life cycle assessment of biogas production from perennial wild plant mixtures and maize (Zea mays L.) in southwest Germany. Issue 8 (27th June 2020) - Lask, Jan; Martínez Guajardo, Alejandra; Weik, Jan; von Cossel, Moritz; Lewandowski, Iris; Wagner, Moritz
Abstract: Maize silage is the main biogas co‐substrate in Germany, but its use is often questioned due to negative environmental impacts. Perennial wild plant mixtures (WPM) are increasingly considered alternatives, as these extensive systems improve soil quality and enhance agrobiodiversity. Methane yields per hectare however do not match those of maize. This study examined whether the potential advantages of replacing maize with WPM for biogas production are counteracted by lower yields and associated effects. Life cycle assessment and life cycle cost assessment were used to compare the environmental and economic performance of electricity generation from WPM in two establishment procedures, 'standard' (WPM E1) and 'under maize' (WPM E2). These metrics were benchmarked against those of maize. The production of 1 kWh electricity was chosen as functional unit. The life cycle inventory of the agricultural phase was based on multi‐annual field trials in southwest Germany. Both WPM E1 and E2 had lower marine eutrophication and global warming potentials than maize. The GWP favourability was however sensitive to the assumptions made with regard to the amount and fate of carbon sequestered in the soil. WPM E1 performed less favourable than WPM E2. This was mainly due to lower yields, which could, in turn, result in potential indirect land use impacts. These impacts may outweigh the carbon sequestration benefits of WPM cultivation. Maize performed best in terms of economic costs, freshwater eutrophication, terrestrial acidification, fine particulate matter and ozone formation. We conclude that the widespread deployment of WPM systems on productive agricultural land should only take place if permanent soil carbon sequestration can be ensured. In either case, WPM cultivation could be a valid alternative for bioenergy buffers and marginal land where competitive yields of common crops cannot be guaranteed, but which could accommodate low‐input cultivation systems. Abstract : Wild plant mixtures (WPM) have been suggested as a potential future biogas substrate. In contrast to the predominant substrate maize silage, these systems could improve soil quality and enhance agrobiodiversity. This study examined whether the potential advantages of replacing maize with WPM could be counteracted by lower yields and associated effects. Life cycle assessment and costing were used to compare the environmental and economic performance of electricity generation from biogas using WPM and maize silage. We conclude that a widespread deployment of WPM systems on productive agricultural land should only take place if permanent soil carbon sequestration can be ensured.